Snakes of the Bhopal district, Madhya Pradesh, India with special reference to road mortality - Manhas, Amit; Raina, Rajni; Wanganeo, Ashwani (Journal of Research in Biology, 2015)
A checklist of snakes observed in the Bhopal district of Madhya Pradesh from March 2013 to September 2015 is documented here. Seventeen species of the snakes belonging to five families were recorded during the current study. All species of snakes were observed, photographed and released back to secure areas away from the human daily interference. In addition, road kills of snakes were also recorded along the forest trails and in urban areas. Out of all the species of snakes Xenochrophis piscator and Ptyas mucosa were found to be the most common snake followed by Amphiesma stolata and Oligodon arnensis.